2015
DOI: 10.5137/1019-5149.jtn.14162-15.2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ozone therapy on experimental vasospasm in the rat femoral artery.

Abstract: Ozone (O 3 ) is a gas that contains three atoms of oxygen with a cyclic structure (5). It induces antioxidant stress and promotes resistance against oxidative stress (13,15) and has been used as an antioxidant agent in inflammation (26). Oxygen-ozone therapy is known to be a bio-oxidative procedure (2) and application of low-dose ozone inhibits prostaglandin synthesis, release of bradykinin and algogenic substances, and proteinase secretion from macrophages and polymorphonuclear leukocytes (8).█ INTRODUCTION … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
0
12
0
7
Order By: Relevance
“…Renal I/R is a primary cause of acute renal failure after transplantation surgery. The findings of a study by Orakdogen et al 34 indicated that the ozoneOPs allowed for a protective element when facing I/R. Following an increase in endothelial NO synthase and inducible NO synthase expression, it was concluded that ozoneOPs were intimately related to the increasing NO production as well as reducing renal damage by suppressing endothelin 1.…”
Section: Echanism Of a Ctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal I/R is a primary cause of acute renal failure after transplantation surgery. The findings of a study by Orakdogen et al 34 indicated that the ozoneOPs allowed for a protective element when facing I/R. Following an increase in endothelial NO synthase and inducible NO synthase expression, it was concluded that ozoneOPs were intimately related to the increasing NO production as well as reducing renal damage by suppressing endothelin 1.…”
Section: Echanism Of a Ctionmentioning
confidence: 99%
“…Following an increase in endothelial NO synthase and inducible NO synthase expression, it was concluded that ozoneOPs were intimately related to the increasing NO production as well as reducing renal damage by suppressing endothelin 1. 34 …”
Section: Echanism Of a Ctionmentioning
confidence: 99%
“…The safe dose of ozone is variable depending on the location of therapy and the goal of the treatment (Smith et al, 2017). Currently, it has been proposed that ranging from 10 up to 80 µg/mL of ozone, is beneficial leading to the positive effects and no toxicity, depending on the tissue, shown in in vitro and in vivo in animal models (El-Sawalhi et al, 2013;Frosini et al, 2012;Orakdogen et al, 2016;Thiele et al, 1997;Sweet et al, 1980;Smith et al, 2017). In humans studies, the safe dose range varies between 15 and 50 µg/mL and it will depend on the type and goal of treatment as well as the local of application.…”
Section: Safety Dose and Clinical Protocolmentioning
confidence: 99%
“…При ішемічних процесах знижується кровотік, що призводить до зниження доставки кисню і ішемії/реперфузії. Вони викликають каскад метаболічних порушень, таких як зниження аеробного метаболізму глюкози (зниження рівнів АТФ), запальних змін, які супроводжуються ацидозом тканин і збільшенням кількості вільних радикалів [30,31].…”
Section: резюмеunclassified
“…Озон також зменшує агрегацію тромбоцитів, сприяє утворенню перекису водню (H 2 O 2 ) на ділянці тромбу, зиеньшуючи процеси розвитку тромбозу [32]. Також озонотерапія може бути корисна при лікуванні постгемморагічного вазоспазму [31] у хворих на інсульт. Під впливом озоно-кисневої суміші в крові утворюються озоніди, які переміщуються з потоком крові по всьому організму.…”
Section: резюмеunclassified